The Effect of Progressive Incentive Compensation Strategy on Improving Business Consultant Performance and Company Performance (Case Study of a Premium Vehicle Distributor) - Elsha Parawira Putri; Okder Pendrian (Sean Institute, 2025)
The aim of the study is to establish the effect of performance-based compensation strategies on employee performance and company's profit; a case study in one of premium vehicles distributor. The study has two research objectives. The first is to determine if there is any influence of progressive incentives on the performances of Business Consultants. The second is to find out the effect of the performances of Business Consultant on the company's Profit Before Tax. The study uses a qualitative method by collecting the primary data through a set of interviews involving several business consultants and managers who were working in the Company in 2018 and 2019. Monthly sales productivity, and monthly profit before tax as quantitative data were analyzed and interpreted using the Pearson Correlation method which evaluated the regular relationship between two continuous variables in the study. Data triangulation is used to analyze the results of interviews. The study finds that progressive incentives promote Business Consultants' performances and lead to annual profit before tax increase. The vehicles distributor company itself is a customer driven type of company whose one of its success factors systems is from interactive communication with customers. Business Consultant is a key person that the company must retain as he/she will maintain the company's loyal customers.